THE INFLUENCE OF BRAND IMAGE ON CUSTOMER LOYALTY IN THE FASHION INDUSTRY - Sukma Aditya; Kosasih Kosasih; Salman Ahmad Yani; Alexandre de Sousa Guterres (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This study aims to analyse the influence of brand image on customer loyalty in the fashion industry through a literature review method. The highly competitive fashion industry requires every business actor to build a strong brand image in order to maintain and increase customer loyalty. This study collects and analyses various scientific literature, such as journals, books, and previous research results relevant to the topic. The results of the study indicate that brand image has a significant influence on customer loyalty. A positive brand image can increase customer trust, satisfaction, and emotional attachment, thereby encouraging them to remain loyal and make repeat purchases even when faced with many other brand options. In addition to brand image, other factors such as product quality, price, and marketing strategies also influence customer loyalty; however, brand image remains the primary factor strengthening customers' attachment to fashion brands. Therefore, fashion companies should prioritise strengthening brand image through consistent communication strategies, product innovation, and excellent service to create sustainable customer loyalty.